(untitled) (Asian Business Research, 2021)
Banks locally and abroad have been subject to several financial crises which led top managers to look critically at their current practices in managing the financial resources in order to avoid losses and to prevent giving a negative image to the community of their customers. Parallel to the aforementioned events, banks have been observing an evolution of the banking investment activities in addition to the transformation of the financial market into an open market system. The different events characterized by higher risks and higher demands for financial services have incited banks to explore and emphasize the importance of governance principles. In this study, the researchers will expose the importance of governance and its main principles in the banking systems. The study will also address the aforementioned pertinent to its implementation according to the activities of Basel Committee on banking supervision. The aim of the study is to assess via a quantitative approach the actual governance practices within a convenient sample of Lebanese banks. The outcomes show that the selected banks abide by the principles of Corporate Governance required byBasel as well as by the Central Bank of Lebanon. Results also address the effect of sound governance on the performance of the Banks in question. Findings will serve to issue recommendations about best practices and to encourage the adoption of sound decisions to adopt Corporate Governance principles.